Monitoring and evaluation system design for small medium enterprises development program - Dewi Andriany; Syaiful Bahri (Proceedings of AICS - Social Sciences, 2017)
The development of small business / industry gets serious attention from various circles either government or public, this is inseparable from the role in the absorption of labor and resilience of small businesses against various turmoil, such as the economic crisis of 1997 ago. In addition, small businesses also serve as one of the important sources for economic growth that directly contributes to increase the income of surrounding communities. This research aims to design a monitoring and evaluation system for the SME’s development program. The SME’s development program that expected to develop and improve the competitiveness of SME are training, coaching, marketing, and funding for the SME. Research’s result is a design model of a monitoring and evaluation system that involving government agencies (such as Dinas Koperasi dan UKM), banking (private and state-owned enterprises), private enterprises which is involving university. University involvement is certainly expected to make the SME’s development program successful and efficient. The role of university is to design guidelines and mechanisms of monitoring and evaluation, so as to detect the success or failure of the program.